PENGARUH METODE HYPNOTEACHING TERHADAP KEMAMPUAN IMAJINASI DALAM MENULIS PUISI SISWA KELAS V SD - Rahmad Ampel Gading; Amelia Widya Hanindita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on students who have difficulty starting to write poetry. The main factor causing this is the difficulty in conveying their feelings and ideas through writing. Using a quantitative experimental method, the purpose of this study was to determine whether the hypnotaching method affects the imagination ability of fifth grade students in writing poetry better. The experiment was designed with a one group pretest posttest design. Normality, homogeneity, and paired simple t-test hypothesis tests were used. With a Sig. value (2 tailed) of 0.000 <0.005, the results of the study indicate the influence of the hypnosis learning method. It is expected that students can use their imagination to create writings and works poetry.